Steroid–AuI–NHC Complexes: Synthesis and Antibacterial Activity. (19th May 2017) - Vellé, Alba; Maguire, Ronan; Kavanagh, Kevin; Sanz Miguel, Pablo J.; Montagner, Diego
Abstract: A series of gold(I) pioneer complexes bearing N ‐heterocyclic carbenes and steroid derivatives (ethynylestradiol and ethisterone) with the generic formula [Au(R2 ‐imidazol‐2‐ylidene)(steroid)] (where R=CH3 or CH2 CH2 OCH3 ) were synthesized, and the X‐ray structure of a rare of gold(I)–estradiol derivative is discussed. Toxicity studies reveal notable antibacterial activity of the gold‐based compounds, which is significantly increased in vivo by the presence of the estradiol unit. Toxicity profiling was estimated in vitro versus Gram‐positive ( Staphylococcus aureus ) and Gram‐negative ( Escherichia coli ) bacteria, and in vivo on Galleria mellonella larvae against E. coli . Abstract : The strategic combination of N ‐heterocyclic carbene Au I complexes and estrogen derivatives exhibits an improved in vivo antibacterial activity on larvae of G. mellonella against E. coli . The presence of the steroids is determinant for the increased in vivo activity. This finding presents a pioneering perspective on the search for effective antimicrobial agents, as the results are comparable to those obtained using a mammalian model.